Explosion characteristics and overpressure prediction of hydrogen-doped natural gas under ambient turbulence conditions - Ranran Li; Zhongmo Xu; Mingzhi Li; Shuhong Li; Zhenyi Liu; Zihao Xiu; Qiqi Liu (Case Studies in Thermal Engineering)
Explosions of combustible gases under ambient turbulence exhibit complex flame propagation and overpressure evolution characteristics, posing challenges to explosion safety assessments. In this study, explosion behaviors of hydrogen-doped natural gas under various wind speeds were investigated using a small-scale experimental system. The results show that when the wind speed does not exceed 2 m/s, ambient turbulence promotes flame acceleration and overpressure enhancement, with the maximum overpressure increased by 20.7 % compared to the no-wind condition. However, when the wind speed exceeds 2 m/s, turbulence suppresses flame propagation, leading to a reduction in maximum overpressure by up to 50.5 %. Under early-stage turbulent disturbances, the flame front exhibits instability from the ignition stage, resulting in a continuous transition from laminar to turbulent combustion without a distinct critical instability radius. Furthermore, a modified overpressure prediction model is proposed by incorporating a flame wrinkling factor into the Thomas model and adopting a dimensionless distance treatment from the TNO multi-energy model. The proposed model achieves a root mean square error of 0.140 kPa under various wind speed conditions, demonstrating good predictive accuracy.